2012
DOI: 10.1111/j.1747-0285.2012.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Drugs and Drug Targets Specific to Fatty Acid Metabolic Pathway of Plasmodium falciparum

Abstract: Plasmodium falciparum, a causitive agent of malaria, is the third most prevalent factor for mortility in the world. Falciparum malaria is an example of evolutionary and balancing selection. Because of mutation and natural selection, the parasite has developed resistance to most of the existing drugs. Under such circumstances, there is a growing need to develop new molecular targets in P. falciparum. A four membrane bound organelles called apicoplast, very much similar to that of chloroplast of plants, have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 83 publications
0
12
0
2
Order By: Relevance
“…Yu and co-workers demonstrated that knockouts of various FAS components in P. falciparum and rodent parasite Plasmodium berghei do not inhibit blood-stage growth (12). While exogenous FAs are sufficient for membrane biogenesis in the blood stage (13), recent studies revealed that de novo biosynthesis is exclusively required in the liver stage of the malarial life cycle (12, 14). Few antimalarial drugs, including atovaquone, primaquine, and anti-folates, are effective against both the blood- and liver-stage parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Yu and co-workers demonstrated that knockouts of various FAS components in P. falciparum and rodent parasite Plasmodium berghei do not inhibit blood-stage growth (12). While exogenous FAs are sufficient for membrane biogenesis in the blood stage (13), recent studies revealed that de novo biosynthesis is exclusively required in the liver stage of the malarial life cycle (12, 14). Few antimalarial drugs, including atovaquone, primaquine, and anti-folates, are effective against both the blood- and liver-stage parasites.…”
Section: Introductionmentioning
confidence: 99%
“…The lead compounds identified are structurally different from other inhibitors of FAS in malaria parasites (for a recent Review, see Ref. [28]). Compared with primaquine, the gold-standard, compounds 6g and 5j show at least a fivefold enhanced inhibitory effect on both the development of clinically silent liver-stage as well as disease-inducing erythrocytic blood-stage P. falciparum parasites.…”
Section: Discussionmentioning
confidence: 99%
“…11 In the blood stage, merozoites infect red-blood cells, initiating a replication process that requires exogenous (host-derived) FA to support membrane biogenesis. 12 It was previously thought that both the liver and blood stages of the malarial parasite relied on the uptake of FA from the host. 13,14 However, this paradigm was challenged when FA enzymes ( Fab H, Fab Z, Fab F) capable of de novo biosynthesis were found targeted to the apicoplast, a vestigial nonphotosynthetic plastid.…”
Section: Introductionmentioning
confidence: 99%
“…19,2830 Though the efficacy of some FAS inhibitors against the blood stage is poorly understood, 19 inhibition of the late liver stage, which requires FAS, is thought to be promising for prophylactics. 8,11,12 …”
Section: Introductionmentioning
confidence: 99%